Manajemen Waktu di Dayah - Eva Kristina (Lembaga Pengembangan Kinerja Dosen, 2024)
Time management is planning, organizing and monitoring time productivity. Time is a performance resource that must be managed effectively and efficiently. In the world of education, time is likened to a sword that must be mastered, as well as in the field of tahfidz al-Qur'an, one of which is implemented in Dayah in Aceh, management is really needed to achieve the memorization target. Regarding this, standard data has not been found regarding time management at Dayah, therefore this research seeks to answer the concept of time management, its application, settings and implications for student memorization. This research is a field study using a qualitative approach, carried out at Islamic boarding schools in Aceh. Data analysis techniques are carried out through data reduction, data presentation and data verification. The research results show that the time management concept for tahfidz is prepared/scheduled after evening and evening prayers and memorized deposits after dawn prayers. This time is short, if you look at Dayah's priority which is devoted to memorization. The application of time management is not optimal, students often procrastinate memorizing, they do not recognize the activities (memorization) and the application of time is still not clear. Apart from that, students are less focused on results, and their responses or attitudes are less firm at times. The implications of time management for memorizing the Al-Qur'an in Dayah, in general, can be seen from the increase and changes in students memorizing the Al-Qur'an.